IMPLEMENTASI MANAJEMEN PENDIDIKAN UNTUK MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH MENENGAH PERTAMA : (Studi Deskriptif kualitatif di SMP Mathlaul Anwar Kabupaten Bandung) - Helmawati; Wawan Rilyawan; Murniati; Winda Wulandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The quality of education is one of the key indicators of the success of educational institutions. However, in practice, many schools have yet to implement optimal management of their institutions, which impacts the quality of graduates that do not align with educational goals. This study aims to describe the implementation of management in improving the quality of education at SMP Mathlaul Anwar, Bandung Regency. This research uses a qualitative approach with a case study method. Data collection techniques include interviews, observation, and documentation study. To ensure the validity of the collected data, a triangulation technique is employed. The data analysis techniques used in this study are data reduction, data presentation, and conclusion drawing. The focus of this research includes planning, organizing, directing, and controlling, as well as the impact of management implementation on educational quality improvement. The results show that planning is conducted collaboratively through annual work meetings involving all school stakeholders; organizing is carried out through systematic and clear task distribution; directing is implemented through supervision and professional development of teachers; and controlling is done through regular evaluation of program implementation. These four management functions have proven to have a positive impact on improving educational quality, as reflected in increased teacher discipline, student learning outcomes, and parental involvement in school activities. The conclusion of this study indicates that structured and sustainable management implementation significantly influences the improvement of educational quality in schools.